Clinical and antimicrobial efficiency of the new mean for the oral care under inflammatory periodontal diseases - Kravchenko, L.; Shcherbakov, S.; Chumachenko, V.; Zherebko, A.; Goncharuk, L. (Journal of Education, Health and Sport, 2019)
Violation of microbiocenosis of the oral cavity leads to the development of inflammatory periodontal diseases that presents medical and social problem. The aim of the work: clinical and microbiological ground for local application of developed apigel for oral cavity care in the complex treatment of chronic generalized periodontitis. 42 patients with chronic generalized catarrhal gingivitis and chronic generalized periodontitis of 1st degree and 14 healthy people were conducted clinical studies. All patients were divided into 3 groups: 1 – the control group (healthy patients), 2 – the basic group, patients with inflammatory diseases of periodontium having complex therapy with a local treatment with the new apigel, 3 – the comparison group, patients having a traditional therapy with local use of the dental gel with chamomile. Efficiency of treatment was estimated with clinical, laboratory, microbiological methods of examination. Local application of the new apigel based on propolis (bee glue) in the complex treatment of patients with chronic generalized catarrhal gingivitis and ChGP of the 1st degree favourably affects the clinical symptoms of inflammation in the oral mucous membrane and periodontium, that was manifested in the decline of hygienic and periodontal index figures. As compared with patients who had traditional anti-inflammation therapy with the local use to the dental gel with chamomile, the recovery terms in patients treated with local application of new apigel reduced by 2–8 days. Microbiological studies on background of changed normal microflora in the oral fluid and contents of periodontal pockets in patients with inflammatory diseases of oral mucous membrane and periodontium revealed increase of anaerobic bacteroids, Fusiformis and Prevotellas. In case of local treatment by the “Apisan” gel on the 10-14-th day after the beginning of medical treatment the considerable decline of pathogenic microflora in researched biotopes of patients with inflammatory diseases of the oral cavity, that testifies to the antibacterial action of preparation. The local application of the “Apisan” gel in the complex therapy of inflammatory diseases of oral mucous membrane and periodontium promotes efficiency of medical treatment and reduces terms of renewal of structural-functional integrity of oral mucosa, improves the hygienic state of oral cavity, having bacteriostatic action, lowering the number of pathogenic microorganisms in the oral cavity, removing violations of microbiocenosis of the sulcus.